Portrayals of Bullying in Young Adult Literature: Considerations for Schools - Hughes, Janette; Laffier, Jennifer Lynn (Canadian Journal of Education/Revue canadienne de l’éducation, 2016)
In this article, the authors examine how bullying is portrayed in three recent young adult novels, focusing specifically on whether the information about bullying is accurate, biased, or represents old myths in comparison to current research. The authors conduct a systematic analysis of the following four themes: (1) What is bullying? (2) Who are the bullies? (3) Who are the victims? (4) Who are the bystanders and what role do they play? They conclude by arguing for the inclusion of young adult fiction that deals with sensitive issues as a way to promote awareness, empathy, and social change to empower youth in school settings.